2022
DOI: 10.1186/s12909-022-03436-1
|View full text |Cite
|
Sign up to set email alerts
|

Academic and non-academic predictors of academic performance in medical school: an exploratory cohort study

Abstract: Background Medical schools should also evaluate applicants’ non-academic characteristics in the search for successful students and future physicians, but ideal non-academic criteria have not yet been found. We followed two successive generations of medical students at the University of Split School of Medicine (USSM) to assess both academic and non-academic constructs as predictors of academic performance, defined as medical school grade point average (GPA). We also interviewed some of the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…26 Regarding background characteristics, our findings were in line with previous studies, which found that nonacademic factors did not significantly predict academic performance in medical school. 21,27 Predictions in academic performance have recently drawn substantial attention in the medical education field, especially due to the potential of machine learning techniques that use advanced learning analytics. 15,28,29 For different machine learning techniques, natural language processing was the most commonly used machine learning technique to predict medical students' academic performance based on data extracted mostly from clinical notes with 75% positive prediction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Regarding background characteristics, our findings were in line with previous studies, which found that nonacademic factors did not significantly predict academic performance in medical school. 21,27 Predictions in academic performance have recently drawn substantial attention in the medical education field, especially due to the potential of machine learning techniques that use advanced learning analytics. 15,28,29 For different machine learning techniques, natural language processing was the most commonly used machine learning technique to predict medical students' academic performance based on data extracted mostly from clinical notes with 75% positive prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the studies have investigated several predictors of medical students’ clerkship performance, including their summative scores such as the grade point average during pre-med and pre-clerkship, 14 scores on the medical school entrance exam, 20,21 and the United States Medical Licensing Examination. 20,22 Our findings demonstrated that many individual subjects in the pre-med and basic medical science stages could also be a significant predictor of clerkship performance.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 The accepted applicant should be able to graduate from the medical school and be successful in his/her subsequent professional practice. 8 …”
Section: Introductionmentioning
confidence: 99%
“…Student success serves a critical role in professional educational institutions, as it not only correlates with a more capable professional workforce but is also often used as a metric for institutional performance 1 . A recent surge in investigations seeks to enhance professional student success and determine primary non‐cognitive skills associated with such success, often not easily measured by standardized examinations 2–4 . York et al.…”
Section: Introductionmentioning
confidence: 99%
“…1 A recent surge in investigations seeks to enhance professional student success and determine primary non-cognitive skills associated with such success, often not easily measured by standardized examinations. [2][3][4] York et al delineated six core components to define academic success: satisfaction, academic achievement, acquisition of skills and competencies, attainment of learning objectives, and career success. Growing evidence links such non-cognitive factors as critical for not only academic performance, 5 but physical and psychological wellness [6][7][8] alongside a degree of professional engagement.…”
Section: Introductionmentioning
confidence: 99%